The influence of the Parthenocissus Planch. genus on temperature and moisture conditions of the space under the canopy and support - Hotsii, Nataliya D. (Journal of the Belarusian State University. Ecology, 2020)
The use of tree lianas for vertical greening in cities still causes discussions about their negative impact on the moisture regime of support. The aim of our work was to study the temperature and moisture conditions of the walls of buildings and fences under the canopy of the most common vines of the genus Parthenocissus Planch in Lviv. Changes in the relative humidity of the support in dry sunny weather and after long rainfall are analyzed. The results of the study showed that the vegetation cover has a positive effect on the state of building materials of walls and fences and performs a protective function.